2021
DOI: 10.1093/biolinnean/blaa233
|View full text |Cite
|
Sign up to set email alerts
|

Assortative pairing for boldness and consequences for reproductive success in Montagu’s harrier

Abstract: Behavioural combination within pairs depending on personality and plasticity might influence reproductive success. However, studies testing this hypothesis are rare, especially in the case of monogamous species with bi-parental care in which the sexes exhibit different behavioural roles. In this study, we investigated the pairing patterns for both boldness and boldness plasticity in Montagu’s harriers (Circus pygargus), a species with sex-specific care, and the consequences for their reproductive success. We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…The different distribution of boldness types influenced by the building density may have evolutionary implications for the Montagu's harrier population. A previous study in the same population showed a positive assortative pairing according to boldness (Rabdeau, Badenhausser, et al., 2021). However, no fitness benefit was detected from this pairing pattern, suggesting that it probably results from ecological constraints rather than only sexual selection.…”
Section: Discussionmentioning
confidence: 64%
“…The different distribution of boldness types influenced by the building density may have evolutionary implications for the Montagu's harrier population. A previous study in the same population showed a positive assortative pairing according to boldness (Rabdeau, Badenhausser, et al., 2021). However, no fitness benefit was detected from this pairing pattern, suggesting that it probably results from ecological constraints rather than only sexual selection.…”
Section: Discussionmentioning
confidence: 64%